The Xylitol Applicability and its Effects in Health Area Worldwide: A Bibliometric Analysis Based on Randomized Controlled Trials - Martins, Mariana Leonel (2022)
Objective: To describe and evaluate the xylitol products’ applicability and its effects in the health area worldwide utilizing a bibliometric analysis from randomized controlled trials (RCT) with humans. Material and Methods: Electronic searches were carried out in Medline/PubMed, Scopus, Cochrane Library, Web of Science, and VHL databases. The main data extracted were: year, area of applicability, type of treatment, country, journal, xylitol posology and concentration, presentation form, outcomes, and effects. Results: From 1476 studies, 257 were included. These studies were published between 1973-2021. The majority was carried out in dentistry (73.9%) and under preventive treatment (67.4%). These studies were developed in the USA (15.4%) and published in Caries Research (6.6%). The posology and concentration ranged between 0.004-67 g/day and 0.002-100%, respectively. The xylitol is usually used in the chewing gum form (44.0%), and for antimicrobial activity evaluation (38.5%). A positive effect was observed in 204 studies (79.3%) and was associated with xylitol concentration ≥ 15% (p=0.007). Side effects were reported in 8.2% and were associated with posology ≥ 5 g/day (p=0.03). Conclusion: Most studies with xylitol were conducted to prevent diseases in the dentistry field. The chewing gum form and antimicrobial activity evaluation were more frequent. Most xylitol products have a positive effect, and few studies report side effects.